2016
DOI: 10.1167/iovs.15-18650
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Natural Progression of Keratoconus Using Three-Dimensional Optical Coherence Tomography

Abstract: Chronologic measurements of corneal tomography in keratoconus demonstrated that the progression of steepening at posterior corneal surface was found not only in patients under 30 years but also in older patients, particularly in advanced keratoconus. The rate of progression can be measured by mapping of corneal curvature and thickness using OCT, and the risk of progression was greater in younger patients with steeper Kmax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Moreover, there were no eyes with Rmin > 6.53 mm (equivalent to 51.7 D) required CXL in this age group ( Fig 2). Some researchers have suggested that keratoconus may progress even beyond 30 years of age [16][17][18]; however, they did not categorize patients with respect to the Rmin value at baseline. The present results indicate that mild to moderate keratoconus at the age of 27 years or older should be followed-up; however, frequent follow-up visits are not necessary.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there were no eyes with Rmin > 6.53 mm (equivalent to 51.7 D) required CXL in this age group ( Fig 2). Some researchers have suggested that keratoconus may progress even beyond 30 years of age [16][17][18]; however, they did not categorize patients with respect to the Rmin value at baseline. The present results indicate that mild to moderate keratoconus at the age of 27 years or older should be followed-up; however, frequent follow-up visits are not necessary.…”
Section: Plos Onementioning
confidence: 99%
“…The present results indicate that mild to moderate keratoconus at the age of 27 years or older should be followed-up; however, frequent follow-up visits are not necessary. Eyes with severe keratoconus (especially with a Rmin � 6.73 mm [58.9 D]) should be followed-up closely, even beyond the age of 27 years, as these patients may also develop acute hydrops [17].…”
Section: Plos Onementioning
confidence: 99%
“…[14][15][16] Clinical keratoconus is reliably detected with Placido disk-based corneal topography and even sometimes at slit-lamp examination. 16 Other technologies, such as: corneal tomography (Scheimpflug or dual Scheimpflug devices), 3,13,17 anterior segment optical coherence tomography (AS-OCT), 18,19 biomechanical devices 20,21 that analyse the anterior and posterior corneal surface, full corneal thickness map, epithelial mapping, or corneal biomechanical properties are necessary to complete keratoconus diagnosis. 5,22 Currently, there is no clinically accepted classification allowing eyecare practitioners to clearly differentiate between healthy and keratoconus cornea (especially in early stages), and that could be used in patients' follow-up in suspect (or diagnosed) cases.…”
Section: Keratoconus Detection Diagnosis and Classificationmentioning
confidence: 99%
“…64,65 AS-OCT has been proposed to assess keratoconus patients ( Figure 4); 66 helping to investigate corneal thickness asymmetry, 67 epithelial thickness-distribution characteristics 68 and monitoring progression. 19 AS-OCT could be a promise tool in keratoconus diagnosis (helping to differentiate between fustre and clinical forms of keratoconus of healthy corneas).…”
Section: Corneal Tomographymentioning
confidence: 99%
“…Periodic corneal shape monitoring is currently the main method adopted to determine the progression of corneal thinning and protrusion in KC, and the effectiveness of management techniques such as collagen cross-linking (CXL) and rigid gas permeable lens wear in halting progression. Various corneal shape measurement methods exist including the Placido 4 , 5 , Scheimpflug 6 , 7 , and Optical coherence tomography (OCT) 8 , 9 , all of which need to comply with strict repeatability criteria in order to provide reliable information on progression. Here the typically irregular surface of the keratoconic cornea presents a difficult challenge to achieving good repeatability of tomography measurements.…”
Section: Introductionmentioning
confidence: 99%